2019
DOI: 10.3389/fnins.2019.00877
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Method for Acute Vagus Nerve Stimulation in Experimental Inflammation

Abstract: Neural reflexes regulate inflammation and electrical activation of the vagus nerve reduces inflammation in models of inflammatory disease. These discoveries have generated an increasing interest in targeted neurostimulation as treatment for chronic inflammatory diseases. Data from the first clinical trials that use vagus nerve stimulation (VNS) in treatment of rheumatoid arthritis and Crohn's disease suggest that there is a therapeutic potential of electrical VNS in diseases characterized by excessive inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…Alternatively, those 2 animals could simply be non-responders seen often in acute studies [38,40]. Our data also suggest that the presence of a heart rate response in an implant does not necessarily predict engagement of the anti-inflammatory pathway, which is consistent with previous findings in acute studies [40,84].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Alternatively, those 2 animals could simply be non-responders seen often in acute studies [38,40]. Our data also suggest that the presence of a heart rate response in an implant does not necessarily predict engagement of the anti-inflammatory pathway, which is consistent with previous findings in acute studies [40,84].…”
Section: Discussionsupporting
confidence: 88%
“…The potential wide therapeutic applicability of VNS lies in part in its ability to modulate inflammation, a process thought to underlie the pathogenesis of many common diseases [23][24][25][26]. This effect was first described in a model of LPS endotoxemia, wherein acute VNS suppressed TNF release [19], and has since been established as a functional read-out of the anti-inflammatory action of VNS [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical setting, electrical neural prostheses can modulate, restore, or bypass nerves, with the aim to restore sensory,5 motor, or autonomic functions of the diseased or damaged nervous system 4,6. There are several neuronal prostheses used on a large scale, such as cochlear implants, deep brain stimulators, and a variety of peripheral nerve stimulators for treating inflammatory disorders and chronic pain 7. At present, the scope of new applications of bioelectronic medicine is expanding at a rapid pace 8.…”
Section: Introductionmentioning
confidence: 99%
“…Vagus nerve stimulation (VNS) exerts anti-inflammatory effects in a variety of diseases 18 and is considered a safe and effective therapy for refractory depression, schizophrenia, somatoform disorder, refractory epilepsy, and inflammatory bowel disease. [19][20][21][22][23] Our previous study also revealed that VNS improved consciousness recovery from TBI.…”
Section: Introductionmentioning
confidence: 99%